Youtube Youtube dan Hak Cipta : Legalitas Hak Moral dalam Cover Music Atas Hasil Karya Pemuda Merauke - Yosman Leonard Silubun; Marlyn Jane Alputila (Jurnal Restorative Justice, 2021)
Abstract The speed of the development of internet technology is very fast, not in line with the development of law. In accordance with the motto in the Dutch language "Het recht hink achter de feiten aan" which translates to "law limping following the development of society". Laws must be twisted in various ways in order to answer the growing problem. This is not so different from the laws and regulations regarding copyright, especially in the world of Youtube. Infringement of copyright content in the world of Youtube can be seen in the emergence of song content sung by other people or commonly known as covers. The closing song that is performed in the world of Youtube does not require the name of the composer to be sung again. Based on the above background, the problem that the author will discuss is how the legalism of moral rights for copyright protection in cover content on Youtube? This study uses a juridical empirical research method, with a sociological juridical approach. Namely an approach in legal research that aims to identify and conceptualize law as real and functional in everyday life. And it is hoped that it will produce empirical legal knowledge directly to the object. Based on the provisions of the Copyright Law, moral rights have been increased in a creation. The elaboration of article 5 of the Copyright Law provides guidance on moral rights which states that moral rights are absolute rights owned by the creator to his / her creation. This provision of moral rights covers the inclusion of names or aliases, use of title names, prosecution for the use of works that are distorted and mutated by other parties. The application of moral rights in the Copyright Law does not only use works in everyday life but has also targeted the Internet world specifically in the media of YouTube. Keywords : YouTube, Copyright, Moral Rights